Optimalisasi Dewan Pers dalam Meningkatkan Literasi Media di Masyarakat - Dani, Jeratallah Aram; Syaifullah, Jahid; Sinam, Sinam (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
Mass media is a spectacle and guide for the public that provides informative information and educational entertainment. In this case, the role of the media, the public, is protected by trusted institutions as contained in the Press Law Number 40 of 1999 and the journalistic code of ethics. With this, it is necessary to understand literacy in maintaining the quality of this information. The method is carried out by observing and analyzing reality qualitatively in the field. The results obtained to date are the development of theories and opinions in society as well as the participation of writers in the agenda held by the press council regarding the preparation of media monitoring guidelines in accordance with the Press Law as one of the legitimization of independent institutions. The conclusion from the results and discussion obtained by the author is that good community participation in media literacy is important in supporting the preparation of these guidelines. In several journals discussing the Institute